Viruses and Bioterrorism - Meyer, R.F. (Encyclopedia of Virology, 2008)
The use of viral agents for biological warfare has a long history, which predates their recognition and isolation by culture. Advances in viral culture and virus stabilization made during the second half of the twentieth century raised the level of concern by facilitating the large-scale production of viral agents for aerosol dissemination. Furthermore, the nucleic acid of many viruses, including some that are currently not threats, can be manipulated in the laboratory. Thus, the potential for genetic engineering and misuse of biotechnology is a serious threat. An effective defense against viral agents requires a comprehensive approach including restricting access to viral stocks, detecting deliberately induced disease outbreaks, rapid laboratory identification of viral agents in clinical specimens, preventing person-to-person transmission, using reliable decontamination procedures, and developing effective vaccines and antiviral drugs.